Perception of Musical Tension in Cochlear Implant Listeners - Spangmose, Steffen; Hjortkjær, Jens; Marozeau, Jeremy (Frontiers in Neuroscience, 2019)
Despite the difficulties experienced by cochlear implant (CI) users in perceiving pitch and harmony, it is not uncommon to see CI users listening to music, or even playing an instrument. Listening to music is a complex process that relies not only on low-level percepts such as pitch or timbre, but also on emotional reactions or the ability to perceive musical sequences as patterns of tension and release. CI users engaged in musical activities might experience some of these higher-level musical features. The goal of this study is to evaluate CI users’ ability to perceive musical tension. Nine CI listeners (CIL) and nine normal-hearing listeners (NHL) were asked to rate musical tension on a continuous visual analog slider during music listening. The subjects listened to a 4 minutes recording of a Mozart’s Piano Sonata No. 4 (K282) performed by an experienced pianist. In addition to the original piece, 4 modified versions were also tested to identify which features might influence the responses to music in the two groups. In each version, one musical feature of the piece was altered: tone pitch, intensity, rhythm, or tempo. Surprisingly, CIL and NHL rated overall musical tension in a very similar way in the original piece. However, the results from the different modifications revealed that while NHL ratings were strongly affected by music with random pitch tones (but preserved intensity and timing information), CIL ratings were not. Rating judgments of both groups were similarly affected by modifications of rhythm and tempo. Our study indicates that CI users can understand higher-level musical aspects as indexed by musical tension ratings based on loudness cues. The results suggest that although most CI users have difficulties perceiving pitch, additional music cues such as tempo and dynamics might contribute positively to their experience of music.